Molecular biology and immunology of the 60-kDa stress protein (65-kDa antigen) of Mycobacterium paratuberculosis - Colston, Angela. (The University of Edinburgh, 1994)
M. paratuberculosis infection in sheep causes a chronic granulomatous enteritis, characterised by a massive cellular infiltration of macrophages, epithelioid cells and lymphocytes. Like other mycobacterial infections the predominant immune response is cell-mediated and this response centres on a complex interaction between T cells and macrophages infected with M. paratuberculosis organisms. T cells have been identified as the predominant inducers of the cell mediated immune response to mycobacteria. Stress proteins have been shown to be immunodominant antigens in immune responses to other pathogenic mycobacteria. T cells reactive to stress proteins have been isolated from infected animals. For these reasons, the 60-kDa stress protein of M. paratuberculosis was chosen for the investigation of the immune response to M. paratuberculosis infection in sheep.

In this thesis the DNA encoding the 60-kDa stress protein of M. paratuberculosis was amplified by PCR, sequenced and the ORF of this protein expressed as a fusion protein with glutathione S-transferase. Recombinant M. paratuberculosis 60-kDa stress protein was obtained by cleavage of the fusion protein with the proteolytic enzyme thrombin.

Recombinant M. paratuberculosis 60-kDa stress protein was used to generate polyclonal T and B cell responses in sheep which were assessed by in vitro proliferation and enzyme-linked immunosorbent assays, respectively. In addition, the recombinant protein was used to generate a monoclonal antibody. The assays and reagents generated in this thesis were subsequently used to investigate the immune response to M. paratuberculosis 60-kDa stress protein in ovine paratuberculosis.

This investigation provides preliminary evidence that paratuberculosis-infected animals have T cells that recognise and are capable of responding by proliferation to M. paratuberculosis 60-kDa stress protein in vitro, and that antibodies to this protein could be detected in sera from these animals. Furthermore, M. paratuberculosis 60-kDa stress protein was detected in tissues from infected animals by immunocytochemical analysis. These preliminary findings support a role for M. paratuberculosis 60-kDa stress protein in the ovine immune response to M. paratuberculosis infection.